2017
DOI: 10.1016/j.aim.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Spherical subgroups of Kac–Moody groups and transitive actions on spherical varieties

Abstract: We define and study spherical subgroups of finite type of a Kac-Moody group. In analogy with the standard theory of spherical varieties, we introduce a combinatorial object associated with such a subgroup, its homogeneous spherical datum, and we prove that it satisfies the same axioms as in the finite-dimensional case. Our main tool is a study of varieties that are spherical under the action of a connected reductive group L, and come equipped with a transitive action of a group containing L as a Levi subgroup.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…And G. Pezzini, under the conditions of being G a complex connected reductive algebraic group, B a Borel subgroup and X a normal irreducible variety with an algebraic action of G, constructed an homogenous spherical datum for spherical subgroups H of G and showed that these objects satisfy the critical combinatorial axioms of the homogenous spherical datum for finite-dimensional spherical homogenous spaces G/H. He also proved that the (abstract) homogenous spherical datum for H is invariant under conjugation [208].…”
Section: Kac-moody Algebras: Other Related Topicsmentioning
confidence: 99%
“…And G. Pezzini, under the conditions of being G a complex connected reductive algebraic group, B a Borel subgroup and X a normal irreducible variety with an algebraic action of G, constructed an homogenous spherical datum for spherical subgroups H of G and showed that these objects satisfy the critical combinatorial axioms of the homogenous spherical datum for finite-dimensional spherical homogenous spaces G/H. He also proved that the (abstract) homogenous spherical datum for H is invariant under conjugation [208].…”
Section: Kac-moody Algebras: Other Related Topicsmentioning
confidence: 99%